Implementation of Land Dispute Resolution Policy Through Mediation at The Gayo Lues Land Office - Eva Rahmawati; Siti Hajar; Obed Bida (Universitas Serang Raya, 2023)
The land conflict in Gayo Lues Regency is a development problem requiring a comprehensive resolution. Settlement of land disputes that give rise to this conflict really requires the role of the government to be able to resolve land disputes peacefully, both with the community and with non-governmental third parties. This land dispute case was caused by administrative irregularities in the processing of land ownership documents or documents in the Gayo Lues Regency, which triggered land disputes that eventually became ongoing conflicts. Thus, it is necessary to have a mediation system in resolving land disputes initiated by the government as a neutral party to minimize land conflicts. The government's role is also not only needed as a mediator but also as a facilitator in implementing land dispute resolution policies that must be implemented by all parties involved in the land conflict resolution process. The purpose of this study was to identify and analyze the implementation of land dispute settlement policies through mediation at the Land Office of Gayo Lues District, Aceh Province, and to analyze the inhibiting factors of the performance of the policy. The method used in achieving the objectives of this study is a descriptive research method and is analyzed qualitatively. The results of the study show that the land dispute resolution policy implemented through the mediation system is going well, although there are still several areas in the Gayo Lues Regency that have not been properly socialized regarding this policy. Thus, the regional government represented by the Land Office of Gayo Lues Regency must be more optimal in carrying out socialization related to land dispute settlement policies through a mediation system so as to minimize the occurrence of ongoing land conflicts